The invasion of alien species Miconia crenata (Vahl) Michelang in disturbed/undisturbed lowland mixed dipterocarp and Kerangas forests in Sabah, Malaysia - Thian Yew Loke; James a. Margrove; Berhaman Ahmad; Grace e. Jikim; Alkinson c. Endawie; Syahrir mhd. Hatta; Anis p. Andrew; Colin R. Maycock (ResearchGate, 2023)
Understanding the factors that make a site susceptible to invasion is essential to mitigate the impacts of invasive alien plant species (IAPS) on biodiversity. Miconia crenata is one of the few IAPS that can colonize undisturbed tropical rainforests. In this study, we investigate the abundance of Miconia crenata in disturbed and undisturbed lowland mixed dipterocarp forest and Kerangas forests in Sabah, Malaysia. Three 400 m long transects were established within each of the four sites. The transects ran from the forest edge into the interior, and eight 25 m2 plots were established at fixed distances along each transect. A further twenty 100 m2 plots were established in each of the undisturbed sites of Kabili-Sepilok Forest Reserve. We found that the density of Miconia crenata was significantly lower along the transects in the Kerangas forest, compared to mixed dipterocarp forest. Miconia crenata densities were also significantly lower along transects in the undisturbed forest compared to the disturbed forest. Within the undisturbed sites, Miconia crenata was 13 times more abundant in the mixed dipterocarp forest compared to the Kerangas forest. This difference in Miconia crenata abundance between the two forest types is probably due to soil fertility, with fertile sites more susceptible to invasion by Miconia crenata.